(untitled) (Journal of actual problems of jurisprudence, 2019)
In article questions of the organization of control and supervising activity of executive authorities in the Republic of Kazakhstan are considered. On the basis of the analysis of standard and legal regulation of control in system of executive power problems of increase of efficiency of this legal institute in the Republic of Kazakhstan are staticized. Key words: control, supervision, the executive branch, the shape of the power effi ciency of compliance and enforcement.